Linking phytotechnologies to bioeconomy; varietal screening of high biomass and energy crops for phytoremediation of Cr and Cu contaminated soils - Pošćić, Filip; Fellet, Guido; Fagnano, Massimo; Fiorentino, Nunzio; Marchiol, Luca (Italian Journal of Agronomy, 2019)
Enerbiochem was a project devoted to study new strategies of industrial valorisation of high biomass crops grown on brownfields or contaminated soils not suitable for food production. Chromium and copper accumulation and toxicity were examined in different species of agronomic interest. Cultivars of Brassica carinata A. Braun (7), Brassica juncea (L.) Czern. (4), Brassica napus L. (4), Raphanus sativus L. (4), inbred lines of Helianthus annuus L. (6) and cultivars of Nicotiana tabacum L. (3) were screened for the best genetic materials to be used with the aims: i) to produce the highest biomass in contaminated soils; and ii) possibly to phytoremediate them. Cr and Cu accumulation in shoots were evaluated on 16 days old plants grown for additional 5 days in the presence of either Cr (60 Î¼M) or Cu (2 Î¼M) in hydroponic. They were characterised for Cr and Cu concentrations in roots and shoots, shoot biomass, and total chlorophyll as well. Shoot biomass was significantly lower in Brassica species than in R. sativus, H. annuus and N. tabacum under Cr treatments. On the contrary, under Cu treatments, N. tabacum produced the lowest biomass in respect to other species. Potentially toxic element concentrations varied among genetic material and some genetic material resulted less affected (higher chlorophyll content and shoot biomass) even under higher Cu or Cr concentrations in shoot. Potential candidates within each species, to be used for coupling phytoremediation and biomass production on slightly Cr-Cu potentially contaminated soils are listed.